PEMBERIAN PSIKOEDUKASI SEBAGAI STRATEGI PENINGKATAN SELF-DISCLOSURE SISWA SISWI SMA KARTIKA XX-1 MAKASSAR - Siti Aisyah Nuralifah Marimin; Nafizah Aulia Q Jamil; Alfyola DwiYuan Alexander; Ahmad Ridfah (Universitas Negeri Makassar, 2023)
Adolescence is a period of transition from childhood to adulthood. At partner locations, there are still many teenagers who experience difficulties in expressing themselves both internally and externally which will have an impact on the process of social interaction. In connection with the problems obtained, the implementation team carried out a method of providing psychoeducation, pre-test and post-test about self-disclosure with the theme